2005
DOI: 10.1002/jbm.a.30577
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of SWNT alters in vitro cell‐SWNT interactions

Abstract: Single-walled carbon nanotubes (SWNT) have been the focus of considerable attention as a material with extraordinary mechanical and electrical properties. SWNT have been proposed in a number of biomedical applications, including neural, bone, and dental tissue engineering. In these applications, it is clear that surrounding tissues will come into surface contact with SWNT composites, and compatibility between SWNT and host cells must be addressed. This investigation describes the gross physical and chemical ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 32 publications
3
115
2
1
Order By: Relevance
“…Thus, nanotube toxicology should be evaluated differently than asbestos toxicology under certain conditions. Surface characteristics of MWCNTs, such as functionalization, degree of hydrophobicity, and protein modification, are thought to be important in internalization events (31,(42)(43)(44). The present study used pristine MWCNTs without any chemical functionalization and suspended MWCNTs in saline solution containing albumin as previously described (17).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nanotube toxicology should be evaluated differently than asbestos toxicology under certain conditions. Surface characteristics of MWCNTs, such as functionalization, degree of hydrophobicity, and protein modification, are thought to be important in internalization events (31,(42)(43)(44). The present study used pristine MWCNTs without any chemical functionalization and suspended MWCNTs in saline solution containing albumin as previously described (17).…”
Section: Discussionmentioning
confidence: 99%
“…Surface characteristics of functionalized MWCNTs, such as the degree of hydrophobicity and protein modification, are important for cell internalization. 20,44 Our study showed that nanoparticles functionalized with Fe were phagocytosed more efficiently, thus increasing their cellular damage. Similarly, Vakarelski et al reported that CNTs penetrate membranes of living cells.…”
Section: Discussionmentioning
confidence: 77%
“…66 Glucosamine-functionalized SWCNTs were able to improve the interactions of the cells with SWCNTs. 67 A study conducted on HL60 cells using two types of fluorescent CNTs with FITC-CNTs and biotin submit your manuscript | www.dovepress.com…”
Section: Advantages and Applications Of Functionalized Cntsmentioning
confidence: 99%
“…Functionalized CNT applications conjugates resulted in enhanced membrane translocation with reduced cytotoxicity, 67 and another study also indicated the internalization of fluorescently labeled nanotubes into cells with no apparent toxicity. 68 Similarly, a study conducted on immune-system cells using two classes of fCNTs -one with 1,3-dipolar cycloaddition and another with oxidation/ amidation -showed that both types of fCNTs were taken up by B and T lymphocytes as well as by macrophages in vitro without affecting cell viability.…”
mentioning
confidence: 98%